PENGENDALIAN HAYATI PATOGEN BUSUK AKAR (Ganoderma sp.) PADA ACACIA MANGIUM DENGAN Trichoderma spp. ISOLAT LOKAL SECARA IN VITRO - Fitriani, .; Suryantini, Rosa; Wulandari, Reine Suci (Universitas Tanjungpura, 2017)
Acacia mangium is one of the favorite types of plants in HTI, but in its growth often occurs root rot disease. Ganoderma sp. is one of the root causes of root rot disease. Control can use biological agents such as Trichoderma local isolates. This study aims to determine the power of antagonists and get the best local Trichoderma isolates to control root rot by Ganoderma with in vitro method. The research was conducted at Silviculture Laboratory of Faculty of Forestry, Tanjungpura University for 4 months. The method used is an experimental method. Consists of isolation and characterization of isolates Ganoderma sp. And Trichoderma spp. antagonist test against Ganoderma sp. local isolate Trichoderma spp. consists of 4 treatments namely Trichoderma sp1 (T1), Trichoderma sp2 (T2), Trichoderma sp3 (T3), Trichoderma sp4 (T4). Each treatment was placed in conjunction with Ganoderma sp. On top of the PDA. An antagonistic test was performed with a completely Randmized Design pattern. Each treatment was repeated 3 times so that there were 15 experimental units. The result of the antagonistic inhibitory test of Trichoderma sp. Against Ganoderma sp. Â Shows a different percentage of inhibition. The percentage of inhibition on T1 treatment was 58.06%, T2 was 43.80%, T3 was 48.11% and T4 was 38.09%. The result of variance analysis showed the treatment of isolate Trichoderma spp. Has no significant effect on inhibiting root rot disease pathogen caused by Ganoderma sp. Keywords: Acacia mangium, Ganoderma sp., In Vitro, Trichoderma spp.